2013
DOI: 10.1068/a44598
|View full text |Cite
|
Sign up to set email alerts
|

The Promise of the Affordable Artist's Studio: Governing Creative Spaces in London

Abstract: The role of artists' organisations in populating and popularising postindustrial urban areas is well documented. However, what are less apparent are analyses of how spaces of artistic production are organised and governed in these areas. This paper explores, via an analysis of organisational documents and practices, the techniques used by London-based affordable studio providers to imagine, calculate, and make material low-cost workspace for artists. The argument made is that the negotiation of competing agend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 70 publications
(115 reference statements)
0
5
0
Order By: Relevance
“…The working spaces of contemporary artists are stimulated by an entrepreneurial energy, where flexibility and working-on-the-move cut new trajectories and sketch out new cartographies of affect: the artist-as-global-commuter, the studio-as-network. Each refract mobilised versions of the studio: aggregations of corporate-style professionalism, DIY activism (Relyea, 2013), 'creative hubs', and 'creative industry' reports (Moreton, 2013;Farias and Wilkie, 2016;Busta, 2017).…”
Section: Studio Registersmentioning
confidence: 99%
“…The working spaces of contemporary artists are stimulated by an entrepreneurial energy, where flexibility and working-on-the-move cut new trajectories and sketch out new cartographies of affect: the artist-as-global-commuter, the studio-as-network. Each refract mobilised versions of the studio: aggregations of corporate-style professionalism, DIY activism (Relyea, 2013), 'creative hubs', and 'creative industry' reports (Moreton, 2013;Farias and Wilkie, 2016;Busta, 2017).…”
Section: Studio Registersmentioning
confidence: 99%
“…We refer to social values as the social benefits provided by creativity. According to the literature on creative industries, culture and creativity lead to urban regeneration (Evans & Shaw, 2004), social inclusion (Belfiore, 2002) and social benefits (Moreton, 2013). In Vietnam, we have observed that creative organizations are working closely with selected groups of society which are often marginalized or left behind, helping them to: improve their well-being, foster social and responsible behavior, develop soft skills, stimulate critical and reflexive thinking, address instances of human rights violations, stimulate creativity, create and cultivate positive emotions toward society, and provoke reflections and viewpoints on political issues.…”
Section: Social Valuesmentioning
confidence: 99%
“…There are, however, similarities. Take, for example, the lack of clarity around the meaning or definition of culture and creativity (Neelands and Choe 2010;Pratt 2005); the explicit instrumentalisation of creativity in urban regeneration (Moreton 2013); and the tensions that have been observed between these policies' social goals of inclusion (culture for everyone) and their neoliberal economic goals promoting competitiveness, consumption, meritocracy and the citizen-consumer (Coates 2001;Oakley 2006).…”
Section: Becoming 'Creative'mentioning
confidence: 99%
“…Meanwhile, in the London case, formalised studio providers largely came together as a sector in the early 2000s. The logics behind studio provision which emerged during this period very explicitly instrumentalise the creative workspace in urban regeneration and community development initiatives and are grounded in economic and social benefit rationales (Moreton 2013). Studio providers in this context are increasingly professionalised, repositioning themselves as property developers, providing spaces that are carefully calculated based on affordability but also on goals of revenue generation, while at the same time tending to reinforce classic romanticised ideals of the artist's studio: white walls, high ceilings, self-contained spaces.…”
Section: Diy As a Place-making Tacticmentioning
confidence: 99%